2010
DOI: 10.1371/journal.pone.0011387
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of miRNA* Strand through Evolutionary Analysis: Implication for Degradation As Merely Carrier Strand or Potential Regulatory Molecule?

Abstract: BackgroundDuring typical microRNA (miRNA) biogenesis, one strand of a ∼22 nt RNA duplex is preferentially selected for entry into a silencing complex, whereas the other strand, known as the passenger strand or miRNA* strand, is degraded. Recently, some miRNA* sequences were reported as guide miRNAs with abundant expression. Here, we intended to discover evolutionary implication of the fate of miRNA* strand by analyzing miRNA/miRNA* sequences across vertebrates.Principal FindingsMature miRNAs based on gene fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(164 citation statements)
references
References 46 publications
10
150
0
4
Order By: Relevance
“…If this is the case, a plausible hypothesis is that alterations in the mature microRNA sequence could have more dramatic effects, which is also supported by the high conservation of microRNA sequences between species. 57 This hypothesis is consistent with observations from previous studies of microRNA sequences. 58 The present study identified 4 rare variants flanking the premature MIR185 sequence for which a possible regulatory role could not be excluded.…”
Section: J Psychiatry Neurosci 2014;39(6)supporting
confidence: 93%
“…If this is the case, a plausible hypothesis is that alterations in the mature microRNA sequence could have more dramatic effects, which is also supported by the high conservation of microRNA sequences between species. 57 This hypothesis is consistent with observations from previous studies of microRNA sequences. 58 The present study identified 4 rare variants flanking the premature MIR185 sequence for which a possible regulatory role could not be excluded.…”
Section: J Psychiatry Neurosci 2014;39(6)supporting
confidence: 93%
“…S1 and Table S1). This concurrent induction of miR-149* and miR-149 by ER stress is intriguing, as one strand of the miRNA duplex, in particular, miRNA*, resulting from cleavage of premiRNAs by Dicer, is commonly degraded (27). Although how the complementary pair of miR149/149* are both preserved in melanoma cells remains unknown, the unusual occurrence of miR-149*, particularly its increase in response to ER stress, implicates that it may have a functional role in adaptation of melanoma cells to stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The asterisk following the name indicates non-functional miRNA or passenger strand that is released from the miRNA duplex (biologically active miRNA: passenger miRNA) during miRNA biogenesis (O'Toole et al, 2006). Recent studies have suggested that miRNA* affords potential opportunities for contributing to the regulation network (Guo et al, 2010). The microarray we employed contained probes to 723 human miRNAs, including miRNA*.…”
Section: Resultsmentioning
confidence: 99%